2016
DOI: 10.1002/gps.4553
|View full text |Cite
|
Sign up to set email alerts
|

Taking a positive spin: preserved initiative and performance of everyday activities across mild Alzheimer's, vascular and mixed dementia

Abstract: Objectives: The literature commonly evaluates those daily activities which are impaired in dementia. However, in the mild stages, people with dementia (PwD) are still able to initiate and perform many of those tasks. With a lack of research exploring variations between different dementia diagnoses, this study sought to investigate those daily activities with modest impairments in the mild stages, and how these compare between Alzheimer's disease (AD), vascular dementia (VaD) and mixed dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Previous research has shown how different basic ADLs deteriorate throughout the stages 11,17,21 , with bathing, dressing, and continence for example deteriorating early on. Although IADLs are known to deteriorate largely in the early stages of the disease 31 , comprehensive knowledge on the components of IADLs (initiative and performance) and their decline has been very limited to date 19,20,32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown how different basic ADLs deteriorate throughout the stages 11,17,21 , with bathing, dressing, and continence for example deteriorating early on. Although IADLs are known to deteriorate largely in the early stages of the disease 31 , comprehensive knowledge on the components of IADLs (initiative and performance) and their decline has been very limited to date 19,20,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Improved recognition of dementia and thus improved diagnosis rates are central to governmental policies and worldwide initiatives 42,43 . Future work should further explore how the R-IDDD2 can help in the differential diagnosis of dementia subtypes, in addition to distinguishing between Alzheimer's disease, vascular, and mixed dementia 33 . Considering that different subtypes deteriorate at different speeds 44 , it would be valuable to assess whether the same is the case for the initiative of daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Increased dependency in everyday life is a hallmark of dementia 1 . Whilst deteriorations in basic and instrumental activities of daily living (bADLs/ IADLs) are common in all dementia syndromes, some research indicates that everyday activities deteriorate differently across syndromes 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…These are Alzheimer's disease, vascular dementia and mixed dementia. [2] As the second most common form of dementia in the elderly, vascular dementia (VD) constitutes a heavy burden to the health care systems in ageing societies [1]. VD is a degenerative disease caused by different vascular lesions, which restricts blood supply to individual brain regions [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that there were significant variations among these subtypes. AD is associated with better preserved initiative and performance than VD, according to the Interview for Deteriorations in Daily Living Activities in Dementia [2]. There are numerous studies focused on AD treatment, while VD has so far received very little attention.…”
Section: Introductionmentioning
confidence: 99%